2016
DOI: 10.1200/jco.2015.65.7825
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Impact of Cytoreductive Surgery and Irradiation of Posterior Fossa Ependymoma in the Molecular Era: A Retrospective Multicohort Analysis

Abstract: Posterior fossa ependymoma comprises two distinct molecular variants termed EPN_PFA and EPN_PFB that have a distinct biology and natural history. The therapeutic value of cytoreductive surgery and radiation therapy for posterior fossa ependymoma after accounting for molecular subgroup is not known. MethodsFour independent nonoverlapping retrospective cohorts of posterior fossa ependymomas (n = 820) were profiled using genome-wide methylation arrays. Risk stratification models were designed based on known clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
181
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 176 publications
(193 citation statements)
references
References 31 publications
10
181
0
2
Order By: Relevance
“…A recent series of 820 patients with infratentorial ependymomas from 4 institutions (83% were EPN_PFA and 17% EPN_PFB) demonstrated that GTR improved PFS and OS for both subgroups. 64 Few patients with EPN_PFA did not receive RT, and RT continues to be recommended because of the poor prognosis. Patients with EPN_PFA tumors and STR fared particularly poorly despite RT, and further research is needed to improve prognosis in this group.…”
Section: Intracranial Ependymomasmentioning
confidence: 99%
“…A recent series of 820 patients with infratentorial ependymomas from 4 institutions (83% were EPN_PFA and 17% EPN_PFB) demonstrated that GTR improved PFS and OS for both subgroups. 64 Few patients with EPN_PFA did not receive RT, and RT continues to be recommended because of the poor prognosis. Patients with EPN_PFA tumors and STR fared particularly poorly despite RT, and further research is needed to improve prognosis in this group.…”
Section: Intracranial Ependymomasmentioning
confidence: 99%
“…There is no doubt regarding which factors have the strongest influence on survival from ependymoma since previous studies have confirmed that the molecular subgroup bears the advantage in the prognostic outcome of posterior fossa ependymoma, showing that PFB ependymoma prevailed over PFA in survival [9]. However, there are still other factors that have an influence on the prognostic value of these potential predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Both posterior fossa type A (PFA) and posterior fossa type A (PFB) still benefit from an increased extent of resection [9]. The internationally accepted management protocol involves surgical resection aiming at gross total resection (GTR) followed by radiotherapy to the tumor bed [10].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular profiling of multiple large ependymoma cohorts (namely through Illumina DNA methylation analysis) has allowed for analyses to be made on the impact of molecular subgroup and clinical variables[5,9,11]. A study of four distinct PF ependymoma cohorts revealed that while use radiotherapy is effective in the case of PF-EPN-A tumors that were gross-totally resected, it had limited impact in patients harboring PF-EPN-A ependymoma with a sub-total resection[5].…”
Section: Introductionmentioning
confidence: 99%
“…A study of four distinct PF ependymoma cohorts revealed that while use radiotherapy is effective in the case of PF-EPN-A tumors that were gross-totally resected, it had limited impact in patients harboring PF-EPN-A ependymoma with a sub-total resection[5]. In the same vein, current clinical trial cohorts that are addressing important questions related to other modalities such as the role of chemotherapy (United States - ACNS0831) need to be analyzed in the context of molecular subgroup.…”
Section: Introductionmentioning
confidence: 99%